2020
DOI: 10.1002/edn3.175
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of environmental DNA sampling to detect the occurrence of endangered coho salmon (Oncorhynchus kisutch) in Mediterranean‐climate streams of California's central coast

Abstract: Analysis of environmental DNA (eDNA) has emerged as an important tool for investigating the occurrence and distribution of fish and other species in aquatic environments. However, in lotic systems, uncertainty remains about how environmental factors influence the downstream transport, degradation, and dilution of eDNA, and hence how detection probability varies with distance from the eDNA source. We conducted cage experiments and paired eDNA and snorkel surveys to evaluate the potential for eDNA methods to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…Indeed, this notion was confirmed by Thalinger et al (2020) when they observed attenuation in caged fish eDNA signals with increasing stream discharge. Alternatively, low discharge may insufficiently transport eDNA to sampling locations before decay and settling mechanisms remove it from the system (Shogren et al, 2016; Spence et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, this notion was confirmed by Thalinger et al (2020) when they observed attenuation in caged fish eDNA signals with increasing stream discharge. Alternatively, low discharge may insufficiently transport eDNA to sampling locations before decay and settling mechanisms remove it from the system (Shogren et al, 2016; Spence et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study (data not shown) suggested that the eDNA signal from the hatchery itself (which is hydraulically connected to Scott Creek) is significantly attenuated before reaching the weir (20‐fold reduction, from ~200 copies/ml at the hatchery outflow to ~10 copies/ml at the weir), and a transport study in a nearby watershed suggest similar attenuation of caged O . kisutch eDNA at distance of 1 km (Spence et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the detectability of DNA released from hatching eggs and sampled in the water column may differ between species that deposit eggs above the stream bed and species that construct redds. For example, detection of DNA from eggs deposited above the stream bed may follow a characteristic pattern where DNA concentrations are typically highest directly downstream of the source (Jane et al, 2015;Spence et al, 2021). In contrast, detection of DNA from redds may resemble species that are buried in stream beds, such as freshwater mussels, where peak DNA concentrations were found to be spatially shifted downstream The timing of life history events has important conservation implications for aquatic species and eDNA surveys can help identify when such events occur.…”
Section: Discussionmentioning
confidence: 99%